2019
DOI: 10.1016/j.jsps.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of subchronic toxicities of mosquito repellents (coils, mats and liquids) on vital organs in Swiss albino mice

Abstract: The aim of the current study was to evaluate and compare the toxicities of different types of mosquito repellents i.e. coils, mats and liquid vapors in animal models. Different types of mosquito repellents including liquid vaporizers, coils and mats have been extensively used by the people to get protection from the mosquitoes and diseases associated with them. The active constituents of these repellents include; allethrins, pyrethrins, paraffin and various other derivatives, are well known for their toxicitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…α-Tocopherol (E307) (Sigma-Aldrich Chemical Company, St. Louis, MO, USA through Bayouni Trading Co. Ltd., Al-Khobar, Saudi Arabia) in water and 0.2 mL Tween ® -80 (Sigma-Aldrich Chemical Company, St. Louis, MO, USA through Bayouni Trading Co. Ltd., Al-Khobar, Saudi Arabia) were mixed to produce a total volume of 10 mL. Doses of 100 mg/kg were administered [22]. A total of 40 healthy male albino mice aged 3-4 months and weighing ≈30 g were maintained in 12 h light-dark cycles at a 24 ± 2 °C temperature and The current study intended to explore the histopathological changes and their remediation in different organs of the experimental animals, i.e., mice exposed to pyrethroids, which humans may encounter when exposed in agro-sector activities, as well as being inhaled from uses of commercially available pyrethroid-formulated products, such as household insecticides and mosquito repellents.…”
Section: Preparation Of the Vitamin Solutions And Experimental Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…α-Tocopherol (E307) (Sigma-Aldrich Chemical Company, St. Louis, MO, USA through Bayouni Trading Co. Ltd., Al-Khobar, Saudi Arabia) in water and 0.2 mL Tween ® -80 (Sigma-Aldrich Chemical Company, St. Louis, MO, USA through Bayouni Trading Co. Ltd., Al-Khobar, Saudi Arabia) were mixed to produce a total volume of 10 mL. Doses of 100 mg/kg were administered [22]. A total of 40 healthy male albino mice aged 3-4 months and weighing ≈30 g were maintained in 12 h light-dark cycles at a 24 ± 2 °C temperature and The current study intended to explore the histopathological changes and their remediation in different organs of the experimental animals, i.e., mice exposed to pyrethroids, which humans may encounter when exposed in agro-sector activities, as well as being inhaled from uses of commercially available pyrethroid-formulated products, such as household insecticides and mosquito repellents.…”
Section: Preparation Of the Vitamin Solutions And Experimental Animalsmentioning
confidence: 99%
“…The pyrethroid constituents cause multifocal congestion, interstitial mononuclear cellular infiltration, cystic dilation in the medulla, and extensive fibrosis in affected animals' kidneys. These toxicants are also known to cause hyperemia, degeneration, and atrophy in cardiac tissues, with extensive noxious effects on the nervous system [18][19][20][21][22]. The current study intended to explore the histopathological changes and their remediation in different organs of the experimental animals, i.e., mice exposed to pyrethroids, which humans may encounter when exposed in agro-sector activities, as well as being inhaled from uses of commercially available pyrethroid-formulated products, such as household insecticides and mosquito repellents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1b). Previous studies also revealed that the exposure of pyrethroid such as prallethrin and allethrin exposure has a direct toxic effect to cells, such as toxic effects include infiltration of testicle tissues by inflammatory cells, degeneration, atrophy, hyperemia, necrosis, and edema tubules with the formation of vacuoles and edematous fluid [16,17]. This causes the diameter of the seminiferous tubules to enlarge.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, mosquito repellents are extensively used in the form of gels, coils, mats, sticks, sprays, transdermal patches, etc. 5 The synthetic chemical components, D-allethrin, D-transallethrin, dimethyl phthalate, transuthrin, DEET (N,Ndiethyl-meta-toluamide), permethrin, piperonyl butoxide, lambda-cyhalothrin, etc. 6 were used as mosquito repellents for combating with these mosquitoes.…”
Section: Introductionmentioning
confidence: 99%